The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1603/an09124
|View full text |Cite
|
Sign up to set email alerts
|

Biology of the Armored ScaleRhizaspidiotus donacis(Hemiptera: Diaspididae), a Candidate Agent for Biological Control of Giant Reed

Abstract: The development, survival, and reproductive output of the armored scale Rhizaspidiotus donacis Leonardi (Hemiptera: Diaspididae) were determined as part of an evaluation of this scale for biological control of giant reed, Arundo donax L. Scale crawlers produced by females collected in southern France and Spain lived for less than two d in the absence of a host. On A. donax shoots held under a diurnally variable temperature regime (15–26°C), crawlers settled on leaf collars and axillary stem bases and completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
1
19
0
1
Order By: Relevance
“…Counts of first-generation scales were combined across sample date dissections (60 or 180 days post-infestation) as prior tests (Moran & Goolsby, 2010) had shown that immature and adult female survival varied little beyond 60 days post-crawler release. Male scales had already completed their development by that time, and were observed in dissections as empty scale covers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Counts of first-generation scales were combined across sample date dissections (60 or 180 days post-infestation) as prior tests (Moran & Goolsby, 2010) had shown that immature and adult female survival varied little beyond 60 days post-crawler release. Male scales had already completed their development by that time, and were observed in dissections as empty scale covers.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key biological control agents released against giant reed is the arundo scale, Rhizaspidiotus donacis Leonardi (Hemiptera: Diaspididae; Goolsby et al, , 2011Moran & Goolsby, 2010). Sessile females produce mobile crawlers that colonise rhizomes and stems where they consume plant cell contents, reducing plant photosynthesis (Moore, Watts, & Goolsby, 2010) and stand vigour (Kirk, Widmer, Campobasso, Carruthers, & Dudley, 2003).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…20A), including the LRGV (Owens and others, 2005;Seawright, Rister, Lacewell, McCorkle, and others, 2009;Seawright, Rister, Lacewell, Sturdivant, and others, 2009). Giant reed displaces native plant species, forms dense monocultures in riparian areas and other wetland habitats, and transpires large amounts of water (Owens and others, 2005;Seawright, Rister, Lacewell, McCorkle, and others, 2009) , and Lasioptera donacis [arundo gall midge]) that might be used to reduce giant reed (e.g., Goolsby and Moran, 2009;Seawright, Rister, Lacewell, McCorkle, and others, 2009;Seawright, Rister, Lacewell, Sturdivant, and others, 2009;Moran and Goolsby, 2010;Poinar and Thomas, 2014). In June 2015, the Governor of Texas signed a bill directing the Texas State Soil and Water Conservation Board to develop a program to eradicate giant reed along the Rio Grande (K. Wahl, pers.…”
Section: Giant Reedmentioning
confidence: 99%
“…Estas observaciones resultaron coincidentes con los estudios sobre su biología desarrollados en las cuarentenas (MORAN & GOOLSBY, 2010). Aunque aún preliminares, estos datos indican que la primera iniciativa de uso de un diaspídido como agente de control biológico para el control de una planta invasora, puede contribuir significativamente a una solución definitiva.…”
Section: Expectativas Y Situación Actualunclassified